Sustainability marketing : new directions and practices - Sharma, Rishi Raj; Kaur, Tanveer; Singh Syan, Amanjot (Emerald Publishing Limited, 2021)
With changing business needs and increased levels of consumer awareness concerning social and ecological issues, organisations need to realign their profitability strategies in order to demonstrate their engagement with sustainable practices. Sustainability Marketing: New directions and practices explores how an increase in customer's desire for sustainable products can form a key part of new marketing strategies. The authors shed new light on strategies that capture the benefits of sustainability from an ecological, social and profitability standpoint in business, while explaining the strategic intent required for building marketing strategies that will provide a competitive advantage. The book harnesses the Triple Bottom Line concept by highlighting the significance of developing, refining, and implementing marketing strategies with a key focus on sustainability, in order to leave a positive impact upon the planet and people. Sustainability Marketing provides solutions to scholars, marketers and decision makers aiming to gain an advantage in businesses where sustainability is increasingly prioritised.
Includes index.
Keywords: Green marketing.; Business & Economics -- Marketing -- General.; Sales & marketing.; elektronické knihy; electronic books